2021
DOI: 10.1371/journal.pone.0249959
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth responses to temporal variation in rainfall differ across a continental-scale climatic gradient

Abstract: Globally, many biomes are being impacted by significant shifts in total annual rainfall as well as increasing variability of rainfall within and among years. Such changes can have potentially large impacts on plant productivity and growth, but remain largely unknown, particularly for much of the Southern Hemisphere. We investigate how growth of the widespread conifer, Callitris columellaris varied with inter-annual variation in the amount, intensity and frequency of rainfall events over the last century and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…This has been documented on a temporal scale where drier sites showed increasing growth sensitivity to PDSI over the last century, paralleled by higher mortality following the ongoing drought in California (Keen et al 2021). Similar changes in growth sensitivity to climate have been reported across precipitation gradients in different functional types (Kannenberg et al 2022) and between different biomes (Hsu et al 2012, Gherardi and Sala 2019, Maurer et al 2020, O'Donnell et al 2021. We would expect these trends to continue given projections of rising temperatures (Zobel et al 2017).…”
Section: Discussionsupporting
confidence: 74%
“…This has been documented on a temporal scale where drier sites showed increasing growth sensitivity to PDSI over the last century, paralleled by higher mortality following the ongoing drought in California (Keen et al 2021). Similar changes in growth sensitivity to climate have been reported across precipitation gradients in different functional types (Kannenberg et al 2022) and between different biomes (Hsu et al 2012, Gherardi and Sala 2019, Maurer et al 2020, O'Donnell et al 2021. We would expect these trends to continue given projections of rising temperatures (Zobel et al 2017).…”
Section: Discussionsupporting
confidence: 74%
“…It is possible that, in ecosystems of intermediate productivity, a preceding wet summer may translate into higher fire risk in successive summers due to biomass build-up [56,161]. Other studies worldwide have reported that such ecosystems are more affected by precipitation variability during the dry season than during the cool season [108,113,177] because cool seasons are not normally water-limited, contrarily to dry seasons, where precipitation increases lead to higher plant productivity and, therefore, more biomass available for burning [59,89,139].…”
Section: Climate Variables and Time Since Previous Firementioning
confidence: 99%
“…A study of the changes in data series of climate variables at annual and monthly scales in the western part of the French Mediterranean area showed that annual precipitation was too low [17]. Moreover, the study stated that monthly rainfalls were decreasing in June and increasing in November throughout the area.…”
Section: Introductionmentioning
confidence: 98%